The influence of halogen-containing modifier on the thermo-oxidative stability of styrene–butadiene–styrene triblock copolymers - I. S. Almatova; K. V. Sukhareva; L. R. Lyusova; S. G. Karpova; T. V. Monakhova; N. O. Belyaeva (Тонкие химические технологии, 2025)
Objectives. Elastomeric materials based on styrene–butadiene–styrene (SBS) triblock copolymers occupy approximately three-quarters of the global thermoplastic elastomer market; in the Russian elastomer market, their share exceeds 80%. Their primary applications include the production of shoe sole materials, anticorrosion coatings, waterproofing, and roofing mastics. The predominant form of degradation of such rubber products, which occurs in the presence of heat and oxygen, is known as thermal-oxidative aging. However, the creation of new functional materials based on modified styrene–butadiene block copolymers will enable the development of materials with enhanced resistance to thermal-oxidative degradation. Chlorinated paraffins, comprising a constituent mixture of polychlorinated n-alkanes, can be applied as halogen-containing modifiers for thermoplastic elastomers to enhance their strength and thermal properties. The aim of the present study is to create climate-resistant elastomeric composite materials based on modified SBS triblock copolymers and investigate the influence of a low molecular weight polychlorinated n-alkane modifier (chlorinated paraffin) on their thermaloxidative stability.Methods. Composite materials based on the SBS triblock copolymers with various amounts of chlorinated paraffin were prepared using the solution blending method. Fourier-transform infrared spectroscopy (FTIR) was used to analyze the impact of the amount of added modifier on the kinetics of thermal-oxidative degradation. The molecular mobility of the elastomers following thermal-oxidation was studied using the paramagnetic probe method to determine the correlation time that characterizes the rotational mobility of the probe in the elastomer matrix. The strength characteristics of the modified elastomer were investigated using a universal testing machine. The kinetics of the thermal-oxidative process were studied using the manometric solid-phase oxidation method.Results. The results show that oxidation of SBS thermoplastic elastomers occurs mainly in the butadiene blocks. The degradation of unmodified elastomers is caused by chemical bond breakage reactions in the macromolecules. However, due to the sensitivity of double bonds in the polybutadiene segment of SBS, this thermoplastic elastomer is susceptible to light, ozone, and heat.Conclusions. The multifunctional effect of the halogen-containing modifier on the elastomer leads to increased thermal-oxidative stability of the SBS triblock copolymer thermoplastic elastomer.